Supply Power Factor Improvement in Ozone Generator System Using Active Power Factor Correction Converter - G. Udhayakumar; Rashmi M R; K. Patel; G.P. Ramesh; Suresh A (Institute of Advanced Engineering and Science, 2015)
Artificial Ozone Generating system needs High Voltage, High Frequency supply. The Ozonator distorts the supply currents and henceforth affect the supply power factor. This paper presents the performance comparison of PWM inverter to Power Factor Corrected (PFC) converter with PWM inverter based High-voltage High-frequency power supply for ozone generator system. The conventional inverter has front end bridge rectifier with smoothing capacitor. It draws non-sinusoidal current from ac mains; as a result input supply has more harmonics and poor power factor. Hence, there is a continuous need for power factor improvement and reduction of line current harmonics. The proposed system has active power factor correction converter which is used to achieve sinusoidal current and improve the supply power factor. The active PFC converter with PWM inverter fed ozone generator generates more ozone output compared to the conventional inverter. Thus the proposed system has less current harmonics and better input power factor compared to the conventional system. The performance of the both inverters are compared and analyzed with the help of simulation results presented in this paper.